228k views
0 votes
Complete the table for the equation y = x -1. Then use the table to graph the equation. -2. -1 0 1 2 6 5 4 3 2. 1 -5 6 -5 4 -3 -2 -1 0 1 2 3 4 5 6

User Arun G
by
5.4k points

1 Answer

2 votes

Given the equation y=x-1, we have the following values for x:


\begin{gathered} x=-2 \\ \Rightarrow y=-2-1=-3 \\ x=-1 \\ \Rightarrow y=-1-1=-2 \\ x=0 \\ \Rightarrow y=0-1=-1 \\ x=1 \\ \Rightarrow y=1-1=0 \\ x=2 \\ \Rightarrow y=2-1=1 \end{gathered}

next, the table should look like this:

and the graph would look like this:

Complete the table for the equation y = x -1. Then use the table to graph the equation-example-1
Complete the table for the equation y = x -1. Then use the table to graph the equation-example-2
User MX D
by
5.4k points